2019
DOI: 10.1681/asn.2019060579
|View full text |Cite
|
Sign up to set email alerts
|

Multicenter Randomized Controlled Trial of Vitamin K Antagonist Replacement by Rivaroxaban with or without Vitamin K2 in Hemodialysis Patients with Atrial Fibrillation: the Valkyrie Study

Abstract: BackgroundVitamin K antagonists (VKAs), although commonly used to reduce thromboembolic risk in atrial fibrillation, have been incriminated as probable cause of accelerated vascular calcification (VC) in patients on hemodialysis. Functional vitamin K deficiency may further contribute to their susceptibility for VC. We investigated the effect of vitamin K status on VC progression in 132 patients on hemodialysis with atrial fibrillation treated with VKAs or qualifying for anticoagulation.MethodsPatients were ran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
145
1
9

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 140 publications
(158 citation statements)
references
References 33 publications
3
145
1
9
Order By: Relevance
“…Otherwise, sequence generation and allocation concealment was deemed unclear if not reported and was high in one trial due to deviation from the intended intervention [ 18 ]. Two trials were at high risk of bias with regard to blinding of participants and personnel based on their open-label study design [ 13 , 14 ]. In the majority of cases, blinding of outcome assessors was deemed either low risk or unclear if it was not specifically reported.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Otherwise, sequence generation and allocation concealment was deemed unclear if not reported and was high in one trial due to deviation from the intended intervention [ 18 ]. Two trials were at high risk of bias with regard to blinding of participants and personnel based on their open-label study design [ 13 , 14 ]. In the majority of cases, blinding of outcome assessors was deemed either low risk or unclear if it was not specifically reported.…”
Section: Resultsmentioning
confidence: 99%
“…Three studies examined changes in coronary artery calcification (CAC) scores. All three found no significant difference with vitamin K supplementation in their intention-to-treat analyses [ 14 , 17 , 19 ]. However, Shea et al found a positive impact of vitamin K1 supplementation on attenuating CAC progression in two subgroups: those who were >85% adherent to the treatment protocol, and those who had pre-existing CAC (baseline Agatston scores ≥10) [ 19 ].…”
Section: Resultsmentioning
confidence: 99%
“…Dp-ucMGP inversely relates to mortality and other clinical meaningful endpoints in various cohorts [12,15,[23][24][25][26][27][28][29][30]. Supplementation of vitamin K has a reducing effect on dp-ucMGP levels [22,31], and the opposite holds true with regard of the use of VKAs [22,[32][33][34]. Furthermore, vitamin K administration decelerated progression of aortic valve calcification [35], arterial stiffness [36], and bone loss [37].…”
Section: Discussionmentioning
confidence: 99%
“…All of these data suggest that coagulation and vascular calcification are interconnected and that the uremic toxins IS and PCS could play an important role herein. However, a recent multicenter randomized controlled trial showed that withdrawal of vitamin K antagonists in hemodialysis patients did not influence progression of arterial calcification progression after 18 months [40]. These conflicting data again indicate that the arterial calcification process is the result of a complex interplay between different pathological pathways.…”
Section: Inflammation and Coagulation Signaling Pathwaysmentioning
confidence: 99%